State secrets privilege visa-vis protection of human rights - Stefanovska, Vesna (Varstvoslovje, 2022)
Purpose: This paper analyses the dilemma regarding secret state privilege and the necessity to protect human rights. The purpose of the paper is to emphasize that in some occasion’s secret state privileges have been used to provide impunity and/or avoid further investigation which can point to acts of torture or acts that are contrary to international human rights law and international criminal law. Design/Methods/Approach: The descriptive method has been used for reviewing primary and secondary sources accompanied with the comparative method in order to make retrospective between different cases. Findings: The results show that human rights are often sacrificed by invoking secret state privilege. Extraordinary renditions have been used to transfer detainees from one state to another without any legal reason for purpose of interrogations which often end with torture. The main question is: should human rights be violated in the name of national security and fighting terrorism? The logical answer is no - the respect for human rights should be the top of the iceberg and no sacrifice can be done when the right to life and prohibition of torture are in question. Indeed, the Zubaydah case triggers the issue related to impunity for acts of torture and oversight on the government and security and intelligence agencies acts. Moreover, it raises questions about the very nature and purpose of secret state privilege by elaborating that even an information that has entered the public domain falls within the secret state privilege. Originality/Value: The content of the article deals with current topic and the controversies which surround the state secret privileges in several cases as well as comparison between different courts’ decisions which have in common the issue of invoking secret state privileges in the name of national security.
Keywords: človekove pravice; extraordinary rendition; human rights; izredne izročitve; mučenje; privilegij državne tajnosti; state secrets privilege; torture